Burnout syndrome in students and professionals of the Occupational Therapy Career of the Central University of Ecuador - Zanafria-Herrera, Demetrio (2023)
Introduction: Burnout syndrome is a very common phenomenon in different work environments; however, prevalence studies in occupational therapy professionals and students are limited. Objective: To establish the presence of Burnout syndrome in students and professionals at practice centers of the Occupational Therapy Career from Universidad Central del Ecuador. Material and methods: Cross-sectional, descriptive, observational study design in 177 students belonging to the Occupational Therapy Career and 35 professionals in the area who work in the practice centers linked to pre-professional practice. Emotional exhaustion, depersonalization and lack of personal fulfillment were determined in each subject using the Maslach Burnout Inventory Scale; the presence of a high level in the emotional exhaustion and depersonalization subscales and a low level of personal fulfillment defines Burnout syndrome. The prevalence of Burnout syndrome in students and professionals and the correlation with years of work practice and gender were calculated. Results: 2.9% (1/35) of the professionals and 4.5% (8/177) of the students presented Burnout syndrome, which was related to the personal environmental variables included in the Maslach scale. From 45.83% to 82.14% of students presented low levels of emotional fatigue and depersonalization; on the other hand, from 37.14% to 52.94% presented average levels of personal fulfillment. Conclusion: The prevalence of Burnout syndrome is low as in professionals as in students of the Occupational Therapy Career who do pre-professional practices in different institutions.